Photoinactivation of Moraxella catarrhalis Using 405‐nm Blue Light: Implications for the Treatment of Otitis Media. (24th April 2020) - Liu, Xiaojing; Chang, Qihang; Ferrer‐Espada, Raquel; Leanse, Leon G.; Goh, Xueping Sharon; Wang, Xiuli; Gelfand, Jeffrey A.; Dai, Tianhong
Abstract: Moraxella catarrhalis is one of the major otopathogens of otitis media (OM) in childhood. M. catarrhalis tends to form biofilm, which contributes to the chronicity and recurrence of infections, as well as resistance to antibiotic treatment. In this study, we aimed to investigate the effectiveness of antimicrobial blue light (aBL; 405 nm), an innovative nonpharmacological approach, for the inactivation of M. catarrhalis OM. M. catarrhalis either in planktonic suspensions or 24‐h old biofilms were exposed to aBL at the irradiance of 60 mW cm −2 . Under an aBL exposure of 216 J cm −2, a >4‐log10 colony‐forming units (CFU) reduction in planktonic suspensions and a >3‐log10 CFU reduction in biofilms were observed. Both transmission electron microscopy and scanning electron microscopy revealed aBL‐induced morphological damage in M. catarrhalis . Ultraperformance liquid chromatography results indicated that protoporphyrin IX and coproporphyrin were the two most abundant species of endogenous photosensitizing porphyrins. No statistically significant reduction in the viability of HaCaT cells was observed after an aBL exposure of up to 216 J cm −2 . Collectively, our results suggest that aBL is potentially an effective and safe alternative therapy for OM caused by M. catarrhalis . Further in vivo studies are warranted before this optical approach can be moved to the clinics. Abstract : Moraxella catarrhalis is one of the major pathogens of pediatric otitis media (OM). This pilot study showed that Moraxella catarrhalis is susceptible to antimicrobial blue light (aBL) at 405 nm. aBL exhibited antimicrobial photoinactivation both in suspensions and in biofilms in vitro, with its possible mechanism of photo‐excitation of endogenous porphyrins in Moraxella catarrhalis cells. Our findings suggest that aBL is a potential effective alternative antimicrobial therapy for OM.